The Extraction Of Tin And Copper From Roasted Copper Dross (RCD) And Copper Dross (CD) - Syed Anwar Idid, Syed Mohd Syafiq Idid (Universiti Sains Malaysia, 2018)
Copper dross (CD) is a by-product from tin smelting process in Malaysia as the result of copper extraction or doping. During smelting processes, the impurities of copper become slag which floats on the molten metal after the addition of sulfur. Roasted Copper Dross (RCD) is the product of roasting of CD. The extraction of tin and copper from copper dross (CD) and roasted copper dross (RCD) by leaching process was carried out by using sulfuric and hydrochloric acid as a leaching agent. The CD and RCD samples was characterized by using XRF, SEM, EDX and XRD. From XRD analysis, due to the nature of CD and RCD as by-product of roasting, it is consist of complex mixture of different phases, where quartz, cassiterite and chalcopyrite peak have been identified. As for XRF results has shown that the RCD sample contain a few major constituents such as tin, copper, sulfur and alumina. In designing leaching process, statistical model using Fractional Factorial Design (FFD) was performed in this study. The leaching parameters such as acid concentration, temperature, type of acids, type of dross (CD and RCD) and stirring rate were investigated. From FFD analysis, it was found that the type of dross and the type of acid are the most significant factor in affecting the recovery of tin. As for the recovery of copper, there is no significant factor was identified. However, leaching time play the major role in affecting the recovery of copper compared to the other factors. The optimum leaching extraction achieved when leaching condition is at 70 ℃ in 1.0 M of HCL using RCD as feed, 450 rpm stirring rate and 6 hours leaching time for copper (28.42% Cu recovery) and at 80 ℃ in 1.2 M of HCL, using CD as feed, 350 rpm stirring rate and 4.5 hours (tin recovery at 31.91 %). As a conclusion, the recovery of Cu and Sn from copper dross by leaching method is viable and this will increase the economic values of waste from tin smelting and further study should be more focus on increasing the recovery of Sn and Cu.